Dual Antiplatelet Therapy in Patients Aged 75 Years and Older with Coronary Artery Disease: A Meta-Analysis and Systematic Review - Garly Saint Croix; Spencer C. Lacy; Amre Gazzhal; Michel Ibrahim; Medeona Gjergjindreaj; Jorge Perez; Malik Shehadeh; Karthik Vedantam; Christian Torres; Nirat Beohar; Esteban Escolar (Journal of Interventional Cardiology)
Objectives. This systematic review and meta-analysis evaluates the safety and efficacy of dual antiplatelet therapy (DAPT) in elderly patients with acute coronary syndrome (ACS). Background. The safety and efficacy of DAPT in elderly patients with ACS is not well characterized. Methods. We performed a systematic literature review to identify clinical studies that reported safety and efficacy outcomes after DAPT for ACS in elderly patients. The primary outcomes of primary efficacy endpoint rates and bleeding event rates were reported as random effects risk ratio (RR) with 95% confidence interval. No prior ethical approval was required since all data are public. Results. Our search yielded 660 potential studies. We included 8 studies reporting on 29,217 patients. There was a higher risk of bleeding event rates in elderly patients treated with prasugrel or ticagrelor when compared to clopidogrel with a risk ratio of 1.17 (95% CI 1.08 to 1.27, p<0.05). There was no difference in primary efficacy endpoint rates between elderly patients treated with prasugrel or ticagrelor when compared to clopidogrel with a risk ratio of 0.85 (95% CI 0.68 to 1.07, p=0.17). Conclusions. This systematic review and meta-analysis suggests that DAPT with prasugrel or ticagrelor compared to clopidogrel is associated with a higher risk of bleeding events in elderly patients with ACS. There was no difference in the primary efficacy endpoints between the two treatment groups.